The Relationship Between The Use Of 3-Month Injection Contraception And The Incidence Of Hypertension In The Working Area Of The Molibagu Community Health Center, South Bolaang Mongondow - Santini, Desak Ketut; Purwati, Anik (Jurnal Maternitas Kebidanan, 2025)
Hypertension is the third leading cause of death in Indonesia due to degenerative diseases. Utilization of contraceptive injections every three months is one of the variables that contributes to the development of hypertension. This research was conducted with the intention of determining whether or not there is a correlation between the use of three-month contraceptive injections and the prevalence of hypertension among women of reproductive age in the Molibagu Community Health Center Working Area, which is located in the South Bolaang Mongondow Regency in the year 2025. Method: The study that was conducted was of the observational analytic kind and used a cross-sectional design. The population of women of reproductive age who are using active contraception in the operating area of ​​the Molibagu Community Health Center in the year 2025, as well as a sample of thirty women of childbearing age who are using contraception that was collected using the accidental sampling approach. To analyze the data, the chi-square test was used. A questionnaire was employed as the tool for the investigation. Results and Discussion:"The results of the study obtained a p-value of 0.000 (p <0.05) which means there is a relationship between the use of 3-month contraceptive injections and the incidence of hypertension. Conclusion: There is a correlation between the use of three months"contraceptive injections and the occurrence of hypertension in women of reproductive age in the Molibagu Community Health Center Working Area, which is located in the South Bolaang Mongondow Regency in the year 2025. We have high hopes that this research will serve as both a source of knowledge and a learning tool in relation to the impact of contraception on blood pressure.